Determination of JONSWAP wave spectral parameters - Preecha Kamronrithisorn; Suphat Vongvisessomjai; Watanabe, Akira; Overbeek, Henk Jen; Canadian Government, Canada (Bangkok : Asian Institute of Technology, 1978)
The Pierson-Moskowitz spectrum for wind generated waves has been widely accepted for application to a fully arisen sea condition. JONSWAP and Mitsuyasu spectra under developing sea are known to be more peaked than the Pierson-Moskowitz spectrum in the neighborhood of spectral peak frequency. The JONSWAP spectrum used for analysis is one-directional three parameter spectrum in term of spectral parameter (a), spectral peak frequency (fm ) and peak enhancement parameter (y) . However, the peak enhancement parameter exhibits no definite relation to dimensionless fetch (gF/U2 10), therefore, this present study aims to analyze JONSWAP spectrum in order to get the actual relationship between them. The analysis can be divided into two types. Firstly, using accepted parameters (a and corresponding f ) in fitting the observed spectra, it m has been shown that variance varies as a function of dimensionless fetch. The variance is found to be equal to 0.0693H2 /3 and 0.0845H2 /3 respectively values of JONSWAP and Mitsuyasu fully arisen sea dimensionless fetch. Secondly, fixing accepted variance to 0.0625 H2 1/3 , the resulting expression for a are found equal to 0.0689 (gF /U2 10 using expressions of spectral peak frequency and significant wave height of JONSWAP and Mitsuyasu respectively The two analysis approaches yield the same order of magnitude of the peak enhancement parameter (y) varying as a function of dimensionless fetch.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1978
Keywords: Spectrum analysis -- Mathematical models; Ocean waves